MPLEMENTASI PROGRAM CSR DAN PENGARUHNYA TERHADAP CITRA PERUSAHAAN (STUDI KASUS PROGRAM CSR PT VALE INDONESIA, TBK PADA PROYEK PENYEDIAAN AIR BERSIH) - Anasrul Anasrul; Muhammad Yunus Amar; Wahda Rasjid (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
In industrial activities in the mining sector usually cause good impact and not good in its implementation. This study aims to evaluate the Implementation of the CSR Program and its Influence on Corporate Image in CSR Program on Pt Vale Indonesia, Tbk on Water Supply Project. This research is explanatory research is research explanation of perception of respondent that aims to analyze the relationship between one variable with other variable or how a variable influence other variable. The results of this study indicate that the three variables ie benefits, welfare, and capacity development have a significant impact on the improvement of corporate image so that it can be concluded that the implementation of CSR program on clean water CSR program in Nuha, Towuti and Wasuponda sub-districts gives positive impact to the improvement of image company